Factors Associated the Psychosocial Stress on Health Workers during the Covid-19 pandemic - Lailatul Khusnul Rizki; Nur Masruroh; Choiruddin Bisri; Esty Puji Rahayu (University of Muhammadiyah Malang, 2022)
Introduction: COVID-19 pandemic has become a severe concern in various countries, including Indonesia; the number of sufferers continues to increase every day. All health services cannot accommodate sufferers to provide emergency health services to provide health services Covid-19 sufferers. These things make health workers at the health facilities at the frontline work tirelessly and continue to provide services until they are physically exhausted and may cause psychological stress, fear, stress, and depression. Objectives: This study aims to describe and analyze the factors that cause psychosocial stress on health workers during a pandemic. Methods: The design of this research is descriptive-analytic with a cross-sectional approach. The population taken is health workers in the southern part of Sidoarjo Regency. The sample obtained is 104 health taken by purposive sampling technique. The instrument used in this study was the GAD-7 (Generalized Anxiety Disorder) anxiety questionnaire with 7 question items. Furthermore, the data will be analyzed using the frequency distribution (percentage) and the chi-square test. Results: There was a relationship of age (p=0,013), workload (p=0,014), knowledge (p=0001), and Availability of personal protective equipment (p=0,346) with the anxiety of health workers. Conclusions: Age, knowledge, and workload influence health worker’s anxiety, so that leaders and management at Health Service Facilities to continue to provide mental health and psychosocial support as an effort to prevent and overcome mental stress conditions for health workers at health facilities in carrying out their duties to treat Covid-19 sufferers.